The use of ICTs in teaching English as a foreign language - Aliaga Perez, Eder Frank (2021)
The objective of this research work is In recent years, the ICTs have been developed from the scientific advances produced in the fields of computer science and telecommunications. ICTs are the set of technologies that allow access, treatment, production and communication of information presented in different codes (text, sound, image). The most representative element of new technologies is mainly the computer and adding to this, the Internet. As different authors affirm, the Internet represents a qualitative leap of great magnitude, redefining and changing the ways of knowing and how man interacts with others. The purpose of this monograph is to explain how teachers can use the ICTs in teaching English as a foreign language within three chapters. The first chapter develops the meaning of ICTs and the tools and non-tools that are related to it. The second chapter is related to the concept of teaching English as a foreign language where it is shown the basic principles and methods to teach English as well as why we do teach it. The third chapter explains the use of ICTs in teaching English as a foreign language in Education, the benefits of applying ICTs in teaching English as a foreign language and finally, the ICTs tools and activities in teaching English as a Foreign Language.